The Implementation of ICT in Teaching Speaking to Students of EFL Class at Faculty of Languages and Literature Universitas Muslim Indonesia - Makmur, Nurul Fajriah; Jafar, Muh. Basri; Salija, Kisman (Celebes Journal of Language Studies, 2024)
This research is qualitative research with the lecturer as the subject and the students in the class taught by the lecturer. Interview forms and observation forms were used as instruments. Interview sheets were given to lecturer and students to determine the perception, implementation and impact of using ICT on students' oral skills. Checklist observation sheet for determining the use of ICT in oral learning and oral skills of students, based on the results of observations of the activities of students during learning by as many people as possible and completed by researchers as observers. Based on the results of data analysis, the results showed that lecturers used two learning media, namely the ICT media used for teaching by lecturers were WhatsApp and Zoom Meeting, the implementation of online learning on the WhatsApp application was implemented poorly, while the implementation of online learning on the Zoom Meeting application is implemented well, the perception of lecturers when teaching using the Whatsapp application shows a low perception, while the perception of lecturers who teach using Zoom Meeting shows a high perception, the speaking performance of students who learn using the Whatsapp application is quite good, meanwhile, students who learn to use the Zoom Meeting application are good.